PENGARUH MOTIVASI DALAM MEMEDIASI HUBUNGAN KESELAMATAN DAN KESEHATAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT SUMBER BARA ABADI - Paembonan, - Pither (EKONOMIA, 2019)
This study aims to determine the effect of occupational safety and health on employee work productivity field engineering PT. Sumber Bara Abadi through motivation as intervening variable.Motivation is a set of traits and values that influence the individual to achieve the specific in accordance with the individual goals. Occupational safety and health are physiological-fiscal and physiological conditions of labor resulting from the work environment provided by the enterprise and work productivity is a measure of efficiency with capital, materials, equipment or technology, HR management, information and time used to produce goods or services.The result of the research is known that the variable of safety and occupational health influence to motivation variable and motivation variable have an effect on productivity variable. In this study, the value of coefficient effect of safety and health on work productivity through motivation of 0.253833 and the value of Zhitung obtained by test sobel 2,269743193 greater than Ztabel 1,960 for significance 0.05.Conclusion known that there is significant effect of safety and health to work productivity of PT. Sumber Bara Abadi through motivation as intervening variable. Thus the proposed hypothesis is proved true.